Long-Distance Obsidian Trade In Indonesia. - Tykot, Robert H.; Chia, Assoc Prof. Dr. Stephen, Ming Soon (1997)
Long-distance trade in obsidian from sources in the southwest Pacific has been well-documented for the Lapita culture complex, beginning about 1600 BC Analyses of obsidian artifacts from recent excavations at Bukit Tengkorak in southeastern Sabah (Borneo, Malaysia) indicate the use of obsidian from multiple sources in Melanesia as early as the 5th millennium BC The archaeological presence of obsidian, up to more than 3500 Ian from its source, is the surviving evidence of what was almost certainly the longest Neolithic trade route in the world. In addition, these results indicate that long-distance trade networks existed in Indonesia at least 2500 years prior to the Lapita culture, and strengthen hypotheses of its origins in southeast Asia.